Plasma polymerization of hexamethyldisiloxane: Investigation of the effect of carrier gas related to the film properties - Chaiwong C. (2014)
In this work we present the influence of carrier gases in the deposition of low-pressure discharge plasma of hexamethyldisiloxane (HMDSO). Plasma polymerized HMDSO films were deposited with an inductively-coupled discharge reactor using Ar and O2 as carrier gases. The films deposited in Ar contained polymeric structure in the form of SiOxCyHz and could significantly improve the barrier to water vapor of poly(lactic acid) (PLA). The SiOx-like structure of HMDSO films was obtained when using O2 as the carrier gas. However, the films supported some state of residual stress leading to film failures and a significant loss of barrier performance of PLA. The formation of organic and inorganic contents in the films was confirmed by X-ray photoelectron spectroscopy (XPS). The discharge power had an effect on the topography of the films. Rough surface with coarse texture was obtained when the process was done in Ar at high discharge powers. On the other hand, the deposition process in O2 induced smoother surface of plasma-polymerized films. © 2012 Elsevier B.V.